THE REJECTION OF ROE v WADE BY THE UNITED STATES SUPREME COURT AFTER FIVE DECADES – A SEISMIC DECISION - George Barrie (Obiter, 2023)
The recent dramatic about-turn of the United States Supreme Court (USSC) in Dobbs v Jackson Women’s Health Organisation (Dobbs) in May 2022 regarding the rights of women in the United States to an abortion has caused a major uproar. Overruling one of the most famous of all USSC cases, Roe v Wade (410 US 113 (1973) (Roe)), five decades after it was decided, has had major repercussions. To fully comprehend the impact that Roe had on the United States, it is opportune to give an overview of Roe, which was a dramatic judgment and became established law for 50 years. In revisiting Roe, it is difficult to understand why such a clear and well-reasoned majority judgment has been overruled. Roe raised serious legal, moral and religious issues. The central issue was whether a woman had a legal right to an abortion. The USSC by a majority of seven to two held that woman had a constitutionally protected right to an abortion. As will be seen, Roe based its decision on its interpretation specifically of the Fourteenth Amendment of the United States Constitution. All major cases before the USSC can be put into two categories – abortion cases and all others. Abortion remains the central legal issue before that court. It defines the judicial philosophies of the justices of the USSC. It dominates their nomination and confirmation processes. The abortion controversy is sensitive and emotional. It generates vigorous, opposing views. It inspires deep and absolute convictions. A person’s philosophy, experiences, exposure to the raw edges of human existence, religious beliefs, and attitudes towards family values, and the moral standards a person establishes and seeks to observe all influence their thinking about abortion. It arguably delineates the difference between the National Democratic and Republican parties. When, during the confirmation proceedings of the present Chief Justice Roberts, he was asked about his views on Roe, he was careful not to commit himself. His answer was that Roe was settled as a precedent of the court and entitled to be respected under the principles of stare decisis, but he added that the justices of the Supreme Court do sometimes reverse their own precedents. Abortion issues remain eternal. Does a woman have a legal right to an abortion? Is the termination of a pregnancy a decision to be made by a woman and her doctor, or is the protection of potential human life a legitimate interest of the State? At what point does an unborn person acquire legal rights that are protected under the law? The majority and dissenting judgments in Roe represent the full spectrum of legal approaches to these and related questions. However, no court decision exists in a vacuum and the controversial issues raised in Roe continue to be raised and debated in the legal and political life of the United States, as they do in other jurisdictions.